2020
DOI: 10.1007/s13318-020-00648-y
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Hydroxychloroquine in COVID-19 Patients: Implications for Dose Optimization

Abstract: Background and Objective In the absence of characterization on pharmacokinetics and reference concentrations for hydroxychloroquine in COVID-19 patients, the dose and treatment duration for hydrochloroquine are currently empirical, mainly based on in vitro data, and may vary across national guidelines and clinical study protocols. The aim of this paper is to describe the pharmacokinetics of hydroxychloroquine in COVID-19 patients, considered to be a key step toward its dosing optimization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…IDENTIFY is the first clinical drug trial that uses a machine learning algorithm to identify subpopulations of patients for whom hydroxychloroquine is associated with a favorable risk-benefit profile. Recent studies have suggested that the variable responses to hydroxychloroquine among COVID-19 patients may be due to factors, such as patient weight and sex [22]. Our work builds on these studies by examining the potential for more complicated combinations of patient characteristics to also impact hydroxychloroquine response.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…IDENTIFY is the first clinical drug trial that uses a machine learning algorithm to identify subpopulations of patients for whom hydroxychloroquine is associated with a favorable risk-benefit profile. Recent studies have suggested that the variable responses to hydroxychloroquine among COVID-19 patients may be due to factors, such as patient weight and sex [22]. Our work builds on these studies by examining the potential for more complicated combinations of patient characteristics to also impact hydroxychloroquine response.…”
Section: Discussionmentioning
confidence: 98%
“…These phenotypes may have important implications for treatment effectiveness. Indeed, pharmacokinetic models have suggested that patient weight and sex impact the metabolism of hydroxychloroquine, with important implications for effective dosing [22]. The CORIST Collaboration has also suggested that patients with elevated c-reactive protein may experience greater benefits from hydroxychloroquine [17].…”
Section: Introductionmentioning
confidence: 99%
“…These results were confirmed by three different studies, enrolling patients with COVID-19 treated with HCQ. First, Mazzanti et al 45 did not document any life-threatening arrhythmic event, with only a modest effect on QTc prolongation, that was attributed to the short duration of HCQ treatment in COVID-19, since HCQ reaches the steady state after 180 days of HCQ therapy 46 . Therefore, caution should be adopted when extending these safety results to patients treated for several years for other indications, that could experience a more severe QTc prolongation and related arrhythmic effects.…”
Section: Mechanisms Of Qt Prolongationmentioning
confidence: 99%
“…Hydroxychloroquine and chloroquine have also received much interest from physicians as a treatment for COVID-19. These compounds have undergone clinical trials as COVID-19 therapeutics [55,56] however, their effectiveness remains questionable.…”
Section: Hydroxychloroquine and Chloroquinementioning
confidence: 99%